The Effect of Online Loans on the Millennial Generation: A Systematic Literature Review (SLR) - Wahyu Puspitasari (Yayasan Riset dan Pengembangan Intelektual, 2024)
Financial service providers, also referred to as financial technology providers, offer digital financial services, such as online loans, which are presently mostly in the form of applications. For those who require money online without having to meet stringent standards or visit the online loan service provider's office, online loans are quite beneficial, especially for members of the millennial age today. This service greatly affects their desire for quick cash for a variety of consumable and productive goals, like starting a new business. All it takes to get money disbursed quickly is to complete an online loan application. Because loans may be repaid in installments with varying interest rates based on the duration chosen, they can also be repaid reasonably easily. Publish Or Perish application secondary data (2018–2023) retrieved through Google Scholar is used in the research methodology. Mapping information data through